Isolated neutropenia: an unexplored side effect of amiodarone - Purnesh, Boppana Venkata; Periyasamy, Manimekalai; Vinatha, Mullangi Chenchu; Alex, J. (International Journal of Advances in Medicine, 2022)
Amiodarone has long been used to treat a variety of arrhythmias. It’s a strong P450 inhibitor, which means it’ll interact with many widely given medications. Unfortunately, it can also produce a wide spectrum of toxicities due to lengthy half-life, immunophilicity, and widespread tissue distribution. Neutropenia associated with mechanistic target of rapamycin (mTOR) inhibitors can be improved by avoiding other medications that cause cytopenias, including proton pump inhibitors (PPIs), H2 blockers and the sulpha group of drugs. A 62-year-old presented in disoriented state and had one episode of involuntary jerky movements. The patient went into atrial fibrillation, was intubated and changed the drug to amiodarone. Before the initiation of amiodarone patient’s blood work seemed to be normal. After 10 days of amiodarone, his hemodynamic status was deranged, and he recovered. Neutropenia is present constantly and reduced to normal only after discontinuation of amiodarone.